The potential health risks of short-chain chlorinated paraffin: A mini-review from a toxicological perspective - Mu, Ying-Wen; Cheng, Dong; Zhang, Cui-Li; Zhao, Xiu-Lan; Zeng, Tao (The Science of the total environment, 2023)
Short-chain chlorinated paraffins (SCCPs) are ubiquitously distributed in various environmental matrics due to their wide production and consumption globally in the past and ongoing production and use in some developing countries. SCCPs have been detected in various human samples including serum, milk, placenta, nail, and hair, and internal SCCP levels were found to be positively correlated with biomarkers of some diseases. While the environmental occurrence has been reported in a lot of studies, the toxicity and underlying molecular mechanisms of SCCPs remain largely unknown. The current tolerable daily intakes (TDIs) recommended by the world health organization/international programme on chemical safety (WHO/IPCS, 100 μg/kg bw/d) and the UK Committee on Toxicity (COT, 30 μg/kg bw/d) were obtained based on a no observed adverse effect level (NOAEL) of SCCP from the repeated-dose study (90 d exposure) in rodents performed nearly 40 years ago. Importantly, the health risks assessment of SCCPs in a variety of studies has shown that the estimated daily intakes (EDIs) may approach and even over the established TDI by UK COT. Furthermore, recent studies revealed that lower doses of SCCPs could also result in damage to multiple organs including the liver, kidney, and thyroid. Long-term effects of SCCPs at environmental-related doses are warranted. [Display omitted] •SCCPs are ubiquitously distributed in environmental matrics.•SCCPs have been detected in various human samples.•The EDIs of SCCPs in studies indicate nonnegligible health risks to residents.•The chronic toxicity of SCCPs at environmentally relevant doses needs to be studied.•The TDI of SCCPs needs to be redefined.